MACROFAUNA - Anita, Muli; Jongkar, Grinang; Cindy, Peter; Jacqleen, Mik; Lee, Nyanti; Ling, Teck Yee; Sim, Siong Fong (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd., 2024)
MACROFAUNA (comprising crustaceans, mollusks, aquatic insects and annelids) constitute an important ecological community in the Baleh basin, regulating ecosystem functions through their activities in nutrient cycles, decomposition and food chains. They occupy a wide range of habitats and show tolerance limit to disturbance and pollution, and therefore, serve as useful biological indicators for stream health assessments. The first major collection of macrofauna made in the Rajang basin was in 2004, which recorded a total of 119 genera comprising marine and freshwater taxa. The survey did not include the Baleh basin.